Application of Information Systems in Web-Based Bucket Sales - Dini Oktaviani; Gesya Nadila; Dylan Revina Sopyan (Universitas Komputer Indonesia, 2023)
The purpose of this research is to see what is the important role of an information system on web-based bucket sales, which can benefit because it will be known by many people. That way the sales of buckets are getting more fans. We use qualitative methods to facilitate the process of analysing objects. The results of this study are that this system can facilitate sellers in marketing buckets so that sales can increase. The process of implementing an information system in selling buckets can be applied by creating a website. So, it can be concluded that information systems have an effect on website-based bucket sales, making it easier to order for buyers.